A Methodology for Building Service-Oriented Applications in the Presence of Non-Functional Properties - Souza Neto, Plácido Antônio de (2012)
This thesis presents ⇡SOD-M (Policy-based Service Oriented Development Methodology), a methodology for modeling reliable service-based applications using policies. It proposes a model driven method with: (i) a set of meta-models for representing non-functional constraints associated to service-based applications, starting from an use case model until a service composition model; (ii) a platform providing guidelines for expressing the composition and the policies; (iii) model-to-model and model-to-text transformation rules for semi-automatizing the implementation of reliable service-based applications; and (iv) an environment that implements these meta-models and rules, and enables the application of ⇡SOD-M. This thesis also presents a classification and nomenclature for non-functional requirements for developing service-oriented applications. Our approach is intended to add value to the development of service-oriented applications that have quality requirements needs. This work uses concepts from the service-oriented development, non-functional requirements design and model-driven delevopment areas to propose a solution that minimizes the problem of reliable service modeling. Some examples are developed as proof of concepts